Syntheses, structures and magnetic properties of nine coordination polymers based on terphenyl-tetracarboxylic acid ligands. Issue 2 (9th December 2016) - Zhou, Xinhui; Chen, Qianqian; Liu, Baolin; Li, Liang; Yang, Tao; Huang, Wei
Abstract : Nine coordination polymers based on dinuclear metal units/metal-carboxylate chains and 1, 1′:4′, 1′′-terphenyl-2′, 4, 4′′, 5′-tetracarboxylic acid have been synthesized and structurally characterized. Complexes2 and9 show the weak ferromagnetic interactions. Abstract : Nine coordination polymers (CPs) [Mn(H3 L)(H2 L)0.5 (phen)] n (1 ), [Ni2 L(phen)2 (μ2 -H2 O)] n (2 ), {[Mn2 L(phen)2 ]·(DMA)(H2 O)} n (3 ), {[Co2 L(μ2 -H2 O)(μ2 -DMA)]·DMF} n (4 ), [CoL0.5 (H2 O)(phen)] n (5 ), {[Ni2 L(μ2 -H2 O)(μ2 -DMA)]·DMA} n (6 ), {[Co2 L(μ2 -H2 O)(μ2 -DMA)]·DMA} n (7 ), {[Ni2 L(μ2 -H2 O)(H2 O)2 (DMF)2 ]·(H2 O)2 (DMF)} n (8 ), and {[Ni4 L2 (μ2 -H2 O)4 (H2 O)2 ]·(H2 O)2 (NMP)} n (9 ) (H4 L = 1, 1′:4′, 1′′-terphenyl-2′, 4, 4′′, 5′-tetracarboxylic acid, DMA = N, N -dimethylacetamine, DMF = N, N -dimethylformamide, NMP = N -methyl-2-pyrrolidone, phen = 1, 10-phenanthroline) have been synthesized and structurally characterized. Crystal structural analyses reveal that1 features the uninodal 2D (4, 4) network with the dinuclear Mn2 (COO)2 units as 4-connected nodes.3 and5 possess the binodal 2D (4, 4) network with dinuclear Mn2 (COO)4 /Co2 O2 units and L 4− ligands as 4-connected nodes, respectively. In2 and8, each dinuclear Ni2 (COO)2 (μ2 -H2 O) unit links to four L 4− ligands and each L 4− ligand bridges four dinuclear Ni2 (COO)2 (μ2 -H2 O) units to generate the 3D framework, which can also be rationalized as a binodal 4, 4-connected (4 2 ·8 4 )(4 2 ·8 4 ) topological network by considering the dinuclear Ni2 (COO)2 (μ2 -H2 O) units as non-planar 4-connected nodes and L 4− ligands as planar 4-connected nodes, respectively. In4, 6–7 and9, there exist a series of parallel-aligned metal-carboxylate chains, which are linked along two directions by para -terphenyl moieties of L 4− ligands to generate the 3D frameworks. Moreover, direct current magnetic susceptibility measurements were carried out to study their magnetic properties. In complexes2 and9, weak ferromagnetic interactions between the magnetic centers were observed. In addition, the other compounds show weak antiferromagnetic exchange interactions between the adjacent metal ions.